Perceived usefulness and appeal of proposed physics projects - Belen, Josefina Gironella (1976)
This study was undertaken for the purpose of investigating perceptions of proposed physics projects in terms of their appeal and usefulness to students by high school students and teachers of physics. The date used were obtained from the responses of teachers and students to the questionnaires used in the survey conducted by the Physics Writing Team of the Science Education Center of the University of the Philippines in January, 1975. There is a strong similarity of perceptions of the appeal and the usefulness of the projects to the students among the teachers and the above average and average students.
Thesis (M.A. Physics Education)--University of the Philippines, Diliman.
Keywords: Physics -- Study and teaching (Secondary) -- Philippines; Physics projects